2017
DOI: 10.1097/pts.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Inpatient Boxed Warning Prescriber Adherence

Abstract: Boxed warning nonadherence is a concern in the inpatient setting, specifically with NSAID use in general medicine patients and antipsychotic use in ICU patients. More than half of boxed warning nonadherence occurred in medications restarted from home, which emphasizes the need for medication evaluation during transitions of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…This indirect mechanism appears to have wildly varying effects. Studies of BBW adherence have found that different patient populations faced BBW violation rates ranging from 0.7% to 56.6% (Lasser et al, 2006;Ricci et al, 2009;Kloet, Lohr, Smithburger, Seybert, & Kane-Gill, 2017). Thus, it appears that FDA can only affect off-label use with great ambiguity.…”
Section: Can Fda Warnings Affect Off-label Use?mentioning
confidence: 99%
“…This indirect mechanism appears to have wildly varying effects. Studies of BBW adherence have found that different patient populations faced BBW violation rates ranging from 0.7% to 56.6% (Lasser et al, 2006;Ricci et al, 2009;Kloet, Lohr, Smithburger, Seybert, & Kane-Gill, 2017). Thus, it appears that FDA can only affect off-label use with great ambiguity.…”
Section: Can Fda Warnings Affect Off-label Use?mentioning
confidence: 99%